Future Directions of Legal Harmonisation and Law Reform : Stormy Seas or Prosperous Voyage ? - Faria, José Angelo Estrella (Uniform Law Review, 2009)

The need to harmonise trade-related laws within countries of the African Union: an introduction to the problems posed by legal divergence - Dlagnekova, Polina (Fundamina : A Journal of Legal History, 2009)
It is widely accepted that inter-state relationships have entered an era of globalisation. The economic theory of convergence explains that it is this phenomenon which has spearheaded, amongst others, the development of international rules in the field of trade, finance and taxation.

Unified Business Laws for Africa: Common Law Perspectives on OHADA - Dickerson, Claire Moore (GMB Publishing Ltd, 2009)

The Role of International Economic Law in Africa - Obale, Offah Ako (Society of International Economic Law (SIEL) Inaugural Conference 2008, 2008)
International Economic law (IEL) has a specific role to play in a complex modern Africa. The underdeveloped state of trade law regimes in Africa is arguably a reflection and product of the low level of commercial activity. The reverse is equally true in that underdevelopment in commercial activity on the continent is a reflection and product of the minimal role played thus far by international economic law.
Keywords: AEC; Africa; African; African Economic Community (AEC); Doha; Globilisation; International Economic Law; OHADA; Trade law; WTO

Reforming Legal Reform in Francophone Africa: World Bank' Project Experience - Wabnitz, Hans-Werner (Islamic Law and Law of the Muslim World Paper, 2008)
You don't plant water lilies in the desert - The keystone of civilized society is justice. Without justice, neither peace nor development. A prerequisite is the populations' trust in legal institutions: the law and the courts. The alienation of the people with imposed legal institutions is the reason for Francophone Africa's lack of justice. To remedy the situation, this paper proposes to reconnect the people with the law through: (1) respecting local values in Village tribunals; (2) reforming lawmaking to comply with custom, accessible (also) in vernacular languages; (3) accessibility of law through the Internet. It is argued that the people, as client of justice, need to regain control over their law in order to respect it. Only then the necessary change of traditions and values is feasible. Women lawyer associations are identified as agents for such change. To redress modern courts, the paper suggests a concentration of tribunals, a tightening of procedure and rigorous control, in order to foster peer pressure for professionalism. The constitutional values are to serve as common bond.
Keywords: ACCESS TO JUSTICE; Africa; Colonial law; Corruption; Court administration; Culture; Customary law; Drafting; Equality; Fatwa; Gender; Honor; Human rights; Institutions; Justice; Law; Legal reform; OHADA; Paralegals; Participation; Reform; Tradition; Uniform Act; Village courts; Worldbank

Some preliminary thoughts on a comparative law model for harmonisation of laws in Africa - Nicholson, Caroline (Fundamina : A Journal of Legal History, 2008)
This paper is premised upon acceptance of the view that some form of harmonisation of laws in Africa is a desirable objective and that comparative legal research is a tool that might effectively be applied in order to further the objective of harmonisation. That said, the time has come for comparatists in Africa to think afresh on the issues of globalisation and the need for harmonisation of laws in Africa, with a view to promoting peace, stability and scope for increased development in the region through greater regional economic co-operation.

NEPAD and African Development: Towards a New Partnership between Development Actors in Africa - Tawfik, Rawia M. (African Journal of International Affairs, 2008)
The model required to drive socio-economic development in Africa, and the relationship between the state and the private sector based on that model, have sparked much controversy among African analysts. Some question the relevance of other successful models of development, such as in the liberal West or in East-Asia, to the African context. Others criticise all models of development that are “alien” to African cultures and conditions hence rejecting the NEPAD model on this basis. This paper argues that although NEPAD does not present a detailed model of the relationship between the state, the private sector and civil society in Africa, some of its theoretical underpinnings suggest a balanced framework that should prompt African scholars to search for new models that do not necessarily imitate already successful ones but respect the particularities of each African state

The Harmonization of Business Law in Africa: Is Article 42 of the OHADA Treaty a Problem? - Enonchong, Nelson (Journal of African Law, 2007)
Keywords: Harmonization; Investment; Member state

Re-Imagining International Law: An Examination of Recent Trends in the Reception of International Law Into National Legal Systems in Africa - Oppong, Richard (Fordham International Law Journal, 2006)
This article suggests that the trend of accepting the supremacy and direct application of international law represents a rethinking of the relationship between international and national law, and that its full implications are yet to be explored. The Article seeks to build on current writings on the subject by analyzing certain regional arrangements and judicial approaches relevant to, but often ignored in the discussion. It attempts not to situate these arrangements or approaches within or outside of the monist/dualist paradigm, but to assess the practical significance of these arrangements for international law, national law, and their respective subjects.

The Social Dimension of Regional Integration in ECOWAS - Robert, René (International Labour Office Working Paper, 2004)
Regional economic integration arrangements have their own purpose, legal framework, institutional set-up, history, and trajectory, and this paper aims to study these factors in relation to the Economic Community of West African States (ECOWAS). When dealing with regional integration, it is important to consider governance, trade liberalization, and its social impact. The paper focuses on the West African Economic and Monetary Union (WAEMU) and the Organization for the Harmonization of Business Law in Africa (OHADA) to analyze labour law harmonization, poverty reduction strategies for development, gender empowerment, and democratic participation. Suggestions to strengthen socio-economic development include promoting social dialogue and how the International Labour Organization and other institutions' can help with better integration in Western Africa. Ultimately, identifying and understanding the unique economic integration arrangements of certain communities can help develop their paths towards a fairer globalization for all.
Keywords: ECOWAS; Integration; Regional; Social dimension; WAEMU

Worldwide Harmonisation of Private Law and Regional Economic Integration - General Report - Basedow, Jürgen (Uniform Law Review, 2003)

Business Law in Africa: OHADA and the Harmonization Process - Martor, Boris; Pilkington, Nanette; Sellers, David S.; Thouvenot, Sébastien (GMB Publishing, 2002)

African Legal Developments in the United States and Sub-Saharan Africa - Eisenfeld, Jamie; Serres, Francois (The International Lawyer, 2001)